2000
DOI: 10.1063/1.373171
|View full text |Cite
|
Sign up to set email alerts
|

Frequency dependence of giant magnetoimpedance effect in CuBe/CoFeNi plated wire with different types of magnetic anisotropy

Abstract: Articles you may be interested inTunable asymmetric magnetoimpedance effect in ferromagnetic NiFe/Cu/Co films Appl. Phys. Lett. 105, 102409 (2014); 10.1063/1.4895708 Magnetoimpedance and magnetization processes of FeCoNi electroplated tubesVery large magnetoimpedance effect in FeCoNi ferromagnetic tubes with high order magnetic anisotropy Magnetoimpedance effect in CoFeNi plated wire with ac field annealing destabilized domain structure A giant magnetoimpedance effect ͑GMI͒ has been measured in a CuBe 0.1 mm d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 10 publications
4
18
0
Order By: Relevance
“…In the case of GMI effect in coated tubes such as the electroplated FeNi, FeNiCo, and CoP microwires, Kurlyandskaya et al [12] found a huge enhancement factor approaching 800% in Fe 20 Co 6 Ni 74 layers (1 µ m-thick) electroplated onto CuBe nonmagnetic microwire (100 µm diameter) at a frequency of 1.5 MHz. That shows the way for producing the largest GMI in these systems.…”
Section: Gmi In Wiresmentioning
confidence: 99%
“…In the case of GMI effect in coated tubes such as the electroplated FeNi, FeNiCo, and CoP microwires, Kurlyandskaya et al [12] found a huge enhancement factor approaching 800% in Fe 20 Co 6 Ni 74 layers (1 µ m-thick) electroplated onto CuBe nonmagnetic microwire (100 µm diameter) at a frequency of 1.5 MHz. That shows the way for producing the largest GMI in these systems.…”
Section: Gmi In Wiresmentioning
confidence: 99%
“…Thus, at low frequencies, the magnetic field distribution in the wire can be found by means of Eqs. (14), (23) (10) and (11). After that, the diagonal and off-diagonal components of the wire impedance can be calculated as …”
Section: Wire Impedance: Low-frequency Approximationmentioning
confidence: 99%
“…Most of previous published papers treated magnetoimpedance on plated wires with a constant magnetic thickness. [9][10][11][12] Up to now no detailed experimental data about the influence of magnetic layer thickness on the GMI effect were given yet, except one report on Cu/CoP wires with CoP thickness D of 3, 4 and 7 mm.…”
Section: Introductionmentioning
confidence: 99%
“…Besides of the uniform wires, ribbons and films, [3][4][5][6][7][8] this effect has been observed in inhomogeneous structured materials such as non -magnetic conducting wire plated with magnetic layers and some sandwich films. [9][10][11][12][13][14][15][16][17][18] Large GMI effect occurs at a relative low frequency in BeCu/NiFe, 9) BeCu/CoFeNi, 10) Ag/NiFe 11) and Cu/CoP 12,13) plated wires. Most of previous published papers treated magnetoimpedance on plated wires with a constant magnetic thickness.…”
Section: Introductionmentioning
confidence: 99%